Telephone or internet delivered talking therapy can alleviate irritable bowel symptoms. (4th November 2019) - Cook, Rob; Davidson, Peter; Martin, Rosie
The study: Everitt H, Landau G, Little P. Therapist telephone-delivered CBT and web-based CBT compared with treatment as usual in refractory irritable bowel syndrome: the ACTIB three-arm RCT. Health Technol Assess 2019;23:1-154. This project was funded by the NIHR Health Technology Assessment Programme (project number 11/69/02). To read the full NIHR Signal, go to https://discover.dc.nihr.ac.uk/content/signal-000784/irritable-bowel-syndrome-helped-by-telephone-or-internet-cbt